PPUPIK PUSAT PRODUKSI BENIH BERSERTIFIKAT UNIVERSITAS MUHAMMADIYAH MAKASSAR - Syamsia, Syamsia; Idhan, Abubakar; Kasifah, Kasifah; Noerfitryani, Noerfitryani (Ngayah: Majalah Aplikasi IPTEKS, 2019)
PPUPIK Pusat Produksi Benih Bersertifikat Unismuh Makassar was established with the aim of meeting the community’s need for quality seed crops according to standards and obtaining certification. This activity was inspired by the results of lecturer research at the University of Muhammadiyah Makassar related to seed production and the development of appropriate technology to support seed production as well as the availability of skilled and trained human resources in carrying out seed production and other appropriate technologies. The main products of PPUPIK Pusat Produksi Benih Bersertifikat Unismuh Makassar are hybrid corn seeds and the additional products are plant seeds, planting media, compost, terrarium, hydroponic installations and hydroponic vegetables. Hybrid corn seeds are produced using crossing technology and production techniques in accordance with technical instructions for hybrid corn seed production. The main seed used is certified seed produced by Balitseral Maros. Product marketing is carried out directly at the PPUPIK Office tower building Iqra,6th Floor,Faculty of Agriculture Muhammadiyah University of Makassar and on line marketing through the website www.ppupikbenihunismuh.com Production sustainability is carried out by forming partnerships with corn farmer groups, and for marketing partnerships with breeding companies. This activity is a place of practice for students of the Faculty of Agriculture’s Department of Agrotechnology and Agribusiness, generating income, and new entrepreneurs as well as developing the entrepreneurial spirit of lecturers and students.